2005
DOI: 10.2460/javma.2005.226.589
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility of Escherichia coli isolates from dairy farms using organic versus conventional production methods

Abstract: Results indicated that compared with isolates from conventional dairy farms, E. coli isolates from organic dairy herds have significantly lower prevalences of resistance to 7 antimicrobials; however, prevalence of resistance was not significantly different for 10 other antimicrobials. Resistance was more common for isolates from calves than for isolates from adult dairy cows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
56
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 21 publications
9
56
4
Order By: Relevance
“…While it is impossible, from our data, to estimate selection coefficients for different antibiotic resistance traits, the difference in proportion of resistance from human and animal isolates is consistent with a higher degree of selection in the human population. It is also notable that the E. coli collected from livestock and poultry came from adult-or market-age animals and is generally higher than reported for similar studies in developed countries (Khachatryan et al, 2004;Sato et al, 2005;Cho et al, 2007). …”
Section: Discussionmentioning
confidence: 62%
“…While it is impossible, from our data, to estimate selection coefficients for different antibiotic resistance traits, the difference in proportion of resistance from human and animal isolates is consistent with a higher degree of selection in the human population. It is also notable that the E. coli collected from livestock and poultry came from adult-or market-age animals and is generally higher than reported for similar studies in developed countries (Khachatryan et al, 2004;Sato et al, 2005;Cho et al, 2007). …”
Section: Discussionmentioning
confidence: 62%
“…For example, significantly higher prevalence of multidrugresistant E. coli was found in animals that were supplied antimicrobials in feed as compared with those from organic farms (66). Two studies have demonstrated associations between antimicrobial use and prevalence of resistant bacteria isolated from consumer food products (41, 58).…”
Section: Cross-sectional Studies On Food Contamination With Antimicromentioning
confidence: 99%
“…Therefore, an infection in one or two animals is often combated by a blanket treatment with antibiotics of the entire house, which may contain over 10,000 animals (Shea, 2004). The farming practice employed may have some bearing on the antibiotic susceptibility of commensal S. aureus; organic farming may result in fewer resistant bacteria than in conventional farms, due to lower exposure to antibiotics and reduced contact between animals (Halbert et al, 2006;Sato et al, 2005;Tikofsky et al, 2003). There is some contrary evidence (Sato et al, 2004), but the continued use of antibiotics in some of the organic farms studied was a possibility (Busato et al, 2000).…”
Section: B Environmental Reservoirs Of Mrsamentioning
confidence: 99%